Local radiotherapy and granulocyte-macrophage colony-stimulating factor to generate abscopal responses in patients with metastatic solid tumours: a proof-of-principle trial. Issue 7 (July 2015) - Golden, Encouse B; Chhabra, Arpit; Chachoua, Abraham; Adams, Sylvia; Donach, Martin; Fenton-Kerimian, Maria; Friedman, Kent; Ponzo, Fabio; Babb, James S; Goldberg, Judith; Demaria, Sandra; Formenti, Silvia C
Summary Background An abscopal response describes radiotherapy-induced immune-mediated tumour regression at sites distant to the irradiated field. Granulocyte-macrophage colony-stimulating factor is a potent stimulator of dendritic cell maturation. We postulated that the exploitation of the pro-immunogenic effects of radiotherapy with granulocyte-macrophage colony-stimulating factor might result in abscopal responses among patients with metastatic cancer. Methods Patients with stable or progressing metastatic solid tumours, on single-agent chemotherapy or hormonal therapy, with at least three distinct measurable sites of disease, were treated with concurrent radiotherapy (35 Gy in ten fractions, over 2 weeks) to one metastatic site and granulocyte-macrophage colony-stimulating factor (125 μg/m2 subcutaneously injected daily for 2 weeks, starting during the second week of radiotherapy). This course was repeated, targeting a second metastatic site. A Simon's optimal two-stage design was chosen for this trial: an additional 19 patients could be enrolled in stage 2 only if at least one patient among the first ten had an abscopal response. If no abscopal responses were seen among the first ten patients, the study would be deemed futile and terminated. The primary endpoint was the proportion of patients with an abscopal response (defined as at least a 30% decrease in the longest diameter of the best responding abscopal lesion). Secondary endpoints were safety and survival. Analyses were done based on intention to treat. The trial has concluded accrual, and is registered with ClinicalTrials.gov, number NCT02474186. Findings From April 7, 2003, to April 3, 2012, 41 patients with metastatic cancer were enrolled. In stage 1 of the Simon's two-stage design, ten patients were enrolled: four of the first ten patients had abscopal responses. Thus, the trial proceeded to stage 2, as planned, and an additional 19 patients were enrolled. Due to protocol amendments 12 further patients were enrolled. Abscopal responses occurred in eight (27·6%, 95% CI 12·7–47·2) of the first 29 patients, and 11 (26·8%, 95% CI 14·2–42·9) of 41 accrued patients (specifically in four patients with non-small-cell lung cancer, five with breast cancer, and two with thymic cancer). The most common grade 3–4 adverse events were fatigue (six patients) and haematological (ten patients). Additionally, a serious adverse event of grade 4 pulmonary embolism occurred in one patient. Interpretation The combination of radiotherapy with granulocyte-macrophage colony-stimulating factor produced objective abscopal responses in some patients with metastatic solid tumours. This finding represents a promising approach to establish an in-situ anti-tumour vaccine. Further research is warranted in this area. Funding New York University School of Medicine's Department of Radiation Oncology and Cancer Institute.